2019
DOI: 10.1002/marc.201900450
|View full text |Cite
|
Sign up to set email alerts
|

Mussel‐Inspired Flexible, Wearable, and Self‐Adhesive Conductive Hydrogels for Strain Sensors

Abstract: delamination of electronic conductors and substrates pose significant challenges in strain sensor applications such as detection of biological signals of human motion. [7] Furthermore, these traditional sensors are mounted on the skin by additional adhesives, mechanical clamps, or straps to achieve long-term practical application. [8] Currently, researchers have focused on identifying new promising candidate materials to overcome these defects.Hydrogels are three-dimensional (3D) polymeric networks with good s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…Ion conductive hydrogels consist of a large number of free ions in a 3D polymer network with similar flexibility as biological systems, making them ideal candidates for wearable flexible devices. In recent studies of self-healing ionic conductive hydrogel flexible sensors, conductive ions such as Fe 3+ , [124,125] Na + , [126][127][128][129] [110] glycerol-plasticized polyvinyl alcohol-borax (PVA-borax) / 0.05 [111] polyvinyl alcohol, phenylboronic acid grafted alginate, and polyacrylamide 1.1 × 10 −2 0.064 [112] polyvinyl alcohol and borax / 0.23 [74] Carbon nanotubes polyacrylamide /chitosan hybrid / 0.06 [113] hydrophobic associated polyacrylamide hydrogel / 0.3 [114] Polyacrylamide hydrogels 0.5 0.91 [115] Silver nanoparticles polyion complex/polyaniline hybrid / 3. Al 3+ , [130] ammonium persulfate, [131] sulfuric acid, [132] and lithium chloride [133,134] have been reported.…”
Section: Conductivity Of Hydrogel Flexible Sensormentioning
confidence: 99%
“…Ion conductive hydrogels consist of a large number of free ions in a 3D polymer network with similar flexibility as biological systems, making them ideal candidates for wearable flexible devices. In recent studies of self-healing ionic conductive hydrogel flexible sensors, conductive ions such as Fe 3+ , [124,125] Na + , [126][127][128][129] [110] glycerol-plasticized polyvinyl alcohol-borax (PVA-borax) / 0.05 [111] polyvinyl alcohol, phenylboronic acid grafted alginate, and polyacrylamide 1.1 × 10 −2 0.064 [112] polyvinyl alcohol and borax / 0.23 [74] Carbon nanotubes polyacrylamide /chitosan hybrid / 0.06 [113] hydrophobic associated polyacrylamide hydrogel / 0.3 [114] Polyacrylamide hydrogels 0.5 0.91 [115] Silver nanoparticles polyion complex/polyaniline hybrid / 3. Al 3+ , [130] ammonium persulfate, [131] sulfuric acid, [132] and lithium chloride [133,134] have been reported.…”
Section: Conductivity Of Hydrogel Flexible Sensormentioning
confidence: 99%
“…second network improved mechanical properties [81] PVA/P(AAm-co-SA) -second network improved mechanical and pH-responsive properties [82] PVA/AG -AG boost self-healing and improved mechanical strength [83] LBG/Gg pH-driven shape memory ultrafast self-healing with high mechanical properties [84] PVA/CST -CST improved machinal properties [85] HA-DP Corsslinked PAAm strain sensors mussel-inspired flexible, wearable, and self-adhesive [86] Other types of borax-based hydrogels oxidized-alginate gelatin injectable in situ forming biodegradable scaffolds for cartilage regeneration and/or treatment of meniscal injuries gelatin create dynamic imine crosslinking with oxidized alginate [87][88][89] PVA/PSA/PNIPAAm thermoresponsive touch sensors PSA/PNIPAAm improved mechanical properties; induce thermo-sensitivity Although the history for the synthesis of polyol/B hydrogels, such as PVA/B [33,40] and galactomannan/B [41] hydrogels, is turned back to the 20 th century, more detailed studies have been performed on the characteristics of these hydrogels in recent years. The stability evaluation of scleroglucan (Sclg)/B hydrogels in aqueous media showed that in high acidic and high alkaline media the stability is reduced significantly.…”
Section: Neat Polyol/borax Hydrogelsmentioning
confidence: 99%
“…Lv et al prepared mussel-inspired flexible, wearable, and self-adhesive conductive hydrogels for strain sensors via the dual crosslinking with borax and free radical copolymerization. [86] First, dopamine (DP) was conjugated to the carboxylate groups of hyaluronic acid (HA). Subsequently, a homogenous aqueous solution of HA-DP, borax, MBA, and AAm was exposed to polymerization using APS/TEMED as initiation system at 4°C.…”
Section: Double-network Borax-based Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, hyaluronic acid (HA) is known for its existence in human body and good biocompatibility. [29][30][31] The combination of HA and DA might offer a stable DPSCs adhesion on the tooth slice, which could be used in pulp tissue regeneration. Herein, by…”
Section: Doi: 101002/marc202000102mentioning
confidence: 99%